11g+3-5g=39

Simple and best practice solution for 11g+3-5g=39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11g+3-5g=39 equation:


Simplifying
11g + 3 + -5g = 39

Reorder the terms:
3 + 11g + -5g = 39

Combine like terms: 11g + -5g = 6g
3 + 6g = 39

Solving
3 + 6g = 39

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 6g = 39 + -3

Combine like terms: 3 + -3 = 0
0 + 6g = 39 + -3
6g = 39 + -3

Combine like terms: 39 + -3 = 36
6g = 36

Divide each side by '6'.
g = 6

Simplifying
g = 6

See similar equations:

| 5(4c-1)-5=18c+8 | | 5y+4a=13 | | 20+14z=11z-20-8 | | -185=-32+17r | | 4s+1k=3r | | 13n=69 | | 11x+24=-2 | | 8z+7=-5z-57 | | 8-n=-4+2(4-n) | | 5.25q-2(3q+1.25)=q+1 | | 4s+k=3r | | 9.2s=12.8s-3.96 | | 3y^2=72 | | -20p=-15.58-11.8p | | (9x-5)-(6x-8)= | | 2m+2n+2m+4n+8= | | 7x-5(5x+4)=142 | | 28M+16=4(4M-23) | | 7y^2-49y=0 | | -3=4x+6minusx | | 2n+8+2n+20= | | -n+25+6n+15=-12 | | 7x+5(5+4)=142 | | d(7-x)=4v | | 16+11v=2v-20+6v | | 10x-31+9x-13=127 | | R+300=-214 | | 152-x=138 | | 3(x+y)=8 | | 1.5(4w+1)=2.5w+1 | | -2n-(n-5)=n+1 | | 2x+4x-4=-2x+4 |

Equations solver categories